1997
DOI: 10.1079/bjn19970092
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetence in relation to a heat-processed diet (Maillard reaction) in weanling rats

Abstract: ~ ~~~~Diets containing unheated casein (CD; control) or a casein-glucose mixture (CGD) previously heated at 140" for 2 h were fed to two groups of young rats for 21 d. Differences in body weight, feed consumption, thymus and spleen growth, protein metabolism and in vivo immune response were then determined. For this last experiment, animals were inoculated with sheep erythrocytes (SRBC) on day 15 to provide an immunological challenge. No changes were seen in body weight, feed consumption or feed conversion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…This means that any loss of these amino acids in GC-I hydrolysate or GC-II hydrolysates might lead to changed immune activities. The Maillard reaction is known to reduce nutritional properties of proteins (Martins, Jongen, & van Boekel, 2000), by reducing bioavailability of several amino acids (especially Lys) (Varela, Arce, Marcos, & Castrillón, 1997). The present study also agreed that GC-I preparation led to Lys loss in GC-I hydrolysate (Table 1).…”
Section: Discussionsupporting
confidence: 78%
“…This means that any loss of these amino acids in GC-I hydrolysate or GC-II hydrolysates might lead to changed immune activities. The Maillard reaction is known to reduce nutritional properties of proteins (Martins, Jongen, & van Boekel, 2000), by reducing bioavailability of several amino acids (especially Lys) (Varela, Arce, Marcos, & Castrillón, 1997). The present study also agreed that GC-I preparation led to Lys loss in GC-I hydrolysate (Table 1).…”
Section: Discussionsupporting
confidence: 78%
“…In animals fed a diet containing casein heated with glucose at different temperatures and for different times, reduced weight gain and delayed growth were reported (Chuyen et al, 1994;Lipka and Ganowiak, 1993). This negative effect, although not always seen (Varela et al, 1997), has been attributed to reduced food intake, diarrhea (O'Brien and Walker, 1988), and antinutritional effects (Finot, 1990). Diarrhea in the test animals was not observed, although rats that consumed diet HC-D had softer feces.…”
Section: Discussionmentioning
confidence: 89%
“…(1992) concluded that the short‐term protein restriction could increase mortality rate of rats because of Salmonella typhimurium infection, whereas the short‐term calorie restriction improved the survival rate. In addition, nutritionally‐mediated immunological disturbances in animals could occur by long‐term consumption of heat‐processed foods (Varela et al., 1997). To maximise production performance and health, therefore, appropriate period of optimum dietary protein consumption and balancing amino acids have to be studied.…”
Section: Introductionmentioning
confidence: 99%